EUROPEAN COURT OF HUMAN RIGHTS AS THE GUARANTOR OF LEGAL PROTECTION OF A HUMAN IN THE FIELD OF AVIATION ACTIVITIES OF UKRAINE - Pyvovar, Yuriy; Bazov, Olexandr (Proceedings of National Aviation University (archive), 2017)
Purpose: The effectiveness of human rights protection in the Council of Europe largely depends on activities of the European Court, which demonstrates high standards of justice, particularly in matters of human rights protection in the field of aviation activities. The article offers a critical assessment of Ukrainian national legislation in terms of its internal legal consistency and compliance with international legal acts. Methods: The methods of legal analysis are used to study court decisions in the aviation field; methods of comparative legal analysis, forecasting and dialectical - in the study of problems in the further improvement of Ukrainian legislation. Also in article applied the theory of legal comparative, approaches to applying the analogy of legal and law in process of making decisions on similar court cases. Results: The article deals with the analysis of the European Court of Human Rights jurisdiction on cases of protection of human rights in the field of aviation activities. Two groups of cases in which Ukraine is a defendant are identified: a) cases of international concern (in particular the Malaysia Airlines’ Boeing 777-200ER crash); b) cases of national character (citizens of Ukraine against the State of Ukraine). The author’s position on deciding the cases in the field of aviation activities is based on the principles of respect for the European Convention on Human Rights, 1950. Discussion: The conclusion about the necessity of amending some national laws, taking into account the legal positions of the European Court (in particular, regarding the right of airlines workers to strike) is made, and the fact that the issues of States and airlines activities to respect human and civil rights in the field of aviation activities are covered by jurisdiction of the European Court of Human Rights and occupy an important place in its practice is indicated.